The Educational Curriculum to Prepare Scholars in Muhammad Natsir’s book Fiqhud Da'wah and Yusuf al-Qaradawi’s book Thaqafah Daiyah - Joko, Ganang Prihatmoko; Saeful Anwar; Akhmad Alim; Abas Mansur Tamam (PT FORMOSA CENDEKIA GLOBAL, 2024)
Islamic higher education should ideally produce a generation proficient in religious knowledge and equipped with skills to navigate contemporary challenges. Unfortunately, the current perception of Islamic higher education is that it possesses low quality, particularly concerning graduates of Islamic studies programs who are considered less capable of keeping up with the pace of modern developments. Consequently, there is a need for a reconstruction of the education system, especially focusing on the curriculum as the foundation of learning, to ensure that educational objectives are achieved optimally. This research aims to examine the curriculum presented in two books: